Whose Knowledge is it Anyway? Epistemic Injustice and the Supervisor/Supervisee Relationship - Dineen, Katy; Thelen, Sarah; Santucci, Anna (Teaching and Learning Inquiry, 2024)
Higher education often acts as a bridge to society, preparing people for future social, political, and economic roles. For many academics, social justice and social inclusion are areas of research interest and teaching expertise. As such, institutions of higher education are well placed to foster reflection on social justice, through research and teaching, and thereby impact the wider society as students take up their roles within it. Yet, higher education itself should be subject to critique from a social justice point of view. Our aim in this article is to provide one such critique. We will focus on PhD research supervision, and in particular the supervisor/supervisee relationship. We will argue that the hierarchical nature of supervision can give rise to injustice. We will use the concepts of epistemic injustice and epistemic power as explanatory tools to clarify what is at issue within dysfunctional supervisor/supervisee relationships. Throughout, we will make use of the mythological story, "The Salmon of Knowledge," to unpack the hierarchies involved in knowledge acquisition/creation. Finally, we will conclude by noting the space within the scholarship of teaching and learning wherein critique of the structures within higher education from a social justice point of view occur, and where there exist potential gaps in this scholarship. Read the corresponding ISSOTL blog post here.